Environmentally-extended input-output analysis for Malaysia / Farah Ayuni Shafie ... [et. al] - Shafie, Farah Ayuni; Suparman, Nursyazwani; Mesarandi, Umi Aida Adlina; Omar, Dasimah (Prof Madya Dr.); Karuppannan, Subramaniam; Leh, Oliver Ling Hoon (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Sustainability has become the key goal in every aspect of the environment especially in the diverse urban systems. Sustainable practices require a controlled setting within an urban system where their practicality and efficacy could be assessed. The aim of the study is to establish an environmental assessment tool based on urban metabolism approach to assist decision-making during environmental and economic assessment in an urban planning process. The outcome provides understanding on the means of integrating carbon footprint and monetary factor to oversee the expenditure of a nation in general, or a household or an individual in particular, in relation to global warming potential. This study applied a retrospective cross sectional study to evaluate sustainability in economic-environmental input-output model for greenhouse gases emission monitoring and climate change adaptation. The potential impact from economic sectors’ contribution on greenhouse gas emissions which eventually leads to global warming and climate change was quantitatively assessed by examining the contribution of greenhouse gas emission from each economic activity. Malaysia greenhouse gas emission of all 120 economic activities is 4.87 kg CO2-eq./cap/day. The use of publicly available data to assemble the matrix representation enables comprehensive assessment of the environmental impacts of a country in a manner which is not only of high technology but also relatively fast and cost effective.